Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Kayu Permata Cibitung - Anggi Oktapiani; Fajri Ariandi; Safrezi Fitra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the current era of globalization, Human resource companies play an important role in advancing business and improving employee performance in a relevant manner. Both superior and subordinate communication, and a clean work environment can affect employee performance. Employee performance is the quality of employee work in completing work that has been given by the company. One of the things that affects employee performance is the work environment and work discipline. The purpose of this study was to determine how far the influence of the work environment and work discipline on the performance of PT Kayu Permata employees. This study uses a descriptive quantitative research method, namely by using multiple linear regression analysis. The results of the study showed a value of of 56.250 > (3.140). So it is stated that the work environment and work discipline obtain a total of of 3.541 which is > from of 1.998 which means is accepted and work discipline obtains of 5.778 > 1.998 so that is accepted. Therefore, the work environment and work discipline greatly influence employee performance.